Oxidative stress in adolescents with overweight/obesity: Oxidative stress in obesity - Bozovic, Marija; Ostanek, Barbara; Kotur-Stevuljevic, Jelena; Marc, Janja; Mercantepe, Filiz; Klisic, Aleksandra (Journal of Medical Biochemistry, 2025)
Aim: The pathophysiological mechanism underlying obesity and related diseases is still incompletely understood. A small number of studies used sophisticated statistical techniques, such as principal component analysis (PCA), to examine the relationship between oxidative stress, cardiometabolic biomarkers, and obesity in adolescent population. Hence, we aimed to explore such a relationship. Methods: A total of 68 adolescents (i.e., 34 were overweight/obese and 34 were sex- and age-matched normal-weight controls) were included in the study. Total oxidant status (TOS) and total antioxidant status (TAS) were measured, whereas their ratios were calculated, i.e., pro-oxidant score [(TOS/TAS)*100] and antioxidant score (TAS/TOS). PCA was applied for reducing the number of determined data by grouping them into factors. Results: A significantly higher concentration of TAS, TOS, and their pro-oxidant ratio (TOS/TAS)*100, while the antioxidant score of TAS/TOS was significantly lower in overweight/obese adolescents compared to normal-weight peers. TOS was the most significant predictor of obesity status (P=0.001). PCA extracted 3 factors related to obesity status: Factor 1 (gender, creatinine, uric acid, total bilirubin, TAS, waist circumference, and urea), Factor 2 (ALT and AST), and Factor 3 (age, glucose, total protein, and TOS). Among them, Factor 2 (P=0.003) and Factor 3 (P=0.003) were independently associated with obesity. Conclusion: The present study provides evidence of disrupted redox homeostasis in adolescents with obesity. Obesity is tightly connected with increased oxidative stress and a cluster of metabolic abnormalities. It is important to recognize risk factors in a timely manner and develop a strategy to fight obesity and associated diseases.